Critical Analysis of Healthcare Policies, Technological Integration, And Economic Sustainability - Alasiri, Abdullah Khalid; Atiq, Aljohani,Adel Ateeq; Abdullah M, Alsuhaimi,; Edah, Alharthi , Meshal; Ibrahim A, Aljohani,; Omar, Taha,Ahmad Hateem; Majed K, Alamri,; Alasiri, Abdulrahman K; Alharbi, Ahlam Salem; Sofi, Soliman Saleh (Journal of Ecohumanism, 2024)
To meet the ever-increasing need for healthcare, there is a need to embrace strong healthcare policies, technological advances, as well as sound economic practices. More so, as the world’s population continues to age, facing crises ranging from pandemic diseases to rising health costs, effective policy adaptation, technological integration, and economic sustainability have become more imminent. This paper aims to have a critical perspective on the implementation of health policies, technology adoption, and managing economic factors based on case studies from various countries. It shows that good healthcare policies and improved technology lead to better health standards as well as improved performance of the systems. It also looks at the economic imperative of nation-states in supporting sustainable healthcare systems. As the findings show, those components should be integrated into a healthcare system to work effectively. Nevertheless, there are high implementation costs, regulatory hurdles, and equity considerations. In the context of understanding how policy reforms work together with technological change and economic planning, the paper makes the following policy recommendations to policymakers.